I am the chosen one: Narcissism in the backdrop of self‐determination theory. Issue 1 (17th July 2018) - Sedikides, Constantine; Ntoumanis, Nikos; Sheldon, Kennon M.
Abstract: Objective: This theoretical article discusses the relevance of self‐determination theory (SDT) for narcissism, a classic topic in self‐theory. Method and Results: The trait of narcissism reflects a self‐aggrandizing, dominant, and manipulative interpersonal orientation that feeds on exaggerated perceptions of agency, but not communion. The article embeds narcissism in the five mini‐theories of SDT (organismic integration, causality orientations, basic needs, cognitive evaluation, and goal contents) and considers research directions that can explore synergies between key constructs from SDT and narcissism. Conclusions: SDT can serve as a foundation for a deeper understanding of narcissism. From the other end, narcissism can enrich SDT by explaining variations in motivational processes.